Children’s Rights in Family Law: Comparative Insights into Best Interests Principles - Azis, Mariya; Mery, Lisa; Basuki, Siti Hatia Adzannya (Legalis : Journal of Law Review, 2025)
This narrative review examines how the principle of the “best interests of the child” is applied across legal systems. Using a thematic synthesis of peer-reviewed literature (2020–2025) from Scopus, Google Scholar, and PubMed, the study explores its implementation in custody, adoption, immigration, child marriage, and non-traditional families. Findings highlight uneven enforcement shaped by patriarchal norms, legal pluralism, and institutional gaps. While European jurisdictions showcase holistic child-centered approaches, many developing countries face persistent challenges. Key recommendations include harmonized legislation aligned with the CRC, guaranteed child participation rights, and systemic reforms that strengthen judicial training, inter-sectoral collaboration, and public awareness. This review contributes by integrating comparative insights across regions and emphasizing the urgency of context-sensitive, rights-based reforms.